Biometric Analysis and Population Structure of Blood Clams (Anadara granosa) in The Bagek Kembar Sekotong Mangrove Ecosystem, West Lombok - Purnamawati, Rena; Karnan; Japa, Lalu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Bagek Kembar Essential Ecosystem (BKEE) is one of the mangrove ecosystem areas located in Cendi Menik Village, Sekotong. West Lombok. The Bagek Kembar mangrove ecosystem is designated as an Essential Ecosystem Area which can be used by the community as a place for catching crabs, shellfish, shrimp and fish incluiri for ecotourism activities. Research on biometrics of blood clams aims to analyze the body biometric distribution of blood clams in the BKEE. Blood clams were taken in the Bagek Kembar Mangrove Ecosystem Area, with a total of 186 individuals at each station. Blood clams were measured on their body parts, namely: shell length, shell width, shell height and weight. The research results showed that the biometrics of the blood clams caught were 12-52 mm long, 10-41 mm wide, 14-54 mm high and 3.5-10.5 grams weight. Judging from the distribution of lengths, the blood clams caught have not yet reached a suitable size for catching because they were dominated by the sizes of under 40 mm (146 individuals), where the suitable size for catching should have a shell size at least 40 mm. Meanwhile, width and height always follow the length, where the length increases. width and height also increase. Meanwhile, the weight distribution has reached the catchable size category with large size of 9.5-10.5 grams as many as 32 individuals.